Phosphatidylinositol 3'-kinase is activated by association with IRS-1 during insulin stimulation. - Backer, J M (1992)
IRS-1 undergoes rapid tyrosine phosphorylation during insulin stimulation and forms a stable complex containing the 85 kDa subunit (p85) of the phosphatidylinositol (PtdIns) 3'-kinase, but p85 is not tyrosyl phosphorylated. IRS-1 contains nine tyrosine phosphorylation sites in YXXM (Tyr-Xxx-Xxx-Met) motifs. Formation of the IRS-1-PtdIns 3'-kinase complex in vitro is inhibited by synthetic peptides containing phosphorylated YXXM motifs, suggesting that the binding of PtdIns 3'-kinase to IRS-1 is mediated through the SH2 (src homology-2) domains of p85. Furthermore, overexpression of IRS-1 potentiates the activation of PtdIns 3-kinase in insulin-stimulated cells, and tyrosyl phosphorylated IRS-1 or peptides containing phosphorylated YXXM motifs activate PtdIns 3'-kinase in vitro. We conclude that the binding of tyrosyl phosphorylated IRS-1 to the SH2 domains of p85 is the critical step that activates PtdIns 3'-kinase during insulin stimulation.